Specificity of the narrative as a form of being of social memory social communities - Halyna Dyakovska (Cхід, 2013)
The article is devoted to the investigation of the narrative as a form of being of social memory. The author considers narrative enables social construction of reality and finding of the basis of being. In the article main characteristics and the main features of narrative as a form of being of social memory are determined.